2012
DOI: 10.1159/000338844
|View full text |Cite
|
Sign up to set email alerts
|

A New and Simple Predictive Formula for Non-Sentinel Lymph Node Metastasis in Breast Cancer Patients with Positive Sentinel Lymph Nodes, and Validation of 3 Different Nomograms in Turkish Breast Cancer Patients

Abstract: Background: Nomogram accuracies for predicting non-sentinel lymph node (SLN) involvement vary between different patient populations. Our aim is to put these nomograms to test on our patient population and determine our individual predictive parameters affecting SLN and non-SLN involvement. Patients and Methods: Data from 932 patients was analyzed. Nomogram values were calculated for each patient utilizing MSKCC, Tenon, and MHDF models. Moreover, using our own patient- and tumor-depended parameters, we establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
(41 reference statements)
0
3
1
4
Order By: Relevance
“…Öz et al (25) reported that Ki-67 and c-erb-B2 expression is connected with non-sentinel metastasis and also two other studies stated cerb-B2 as an independent factor (23,24). We found no direct relation between Ki-67, c-erb-B2, hormone receptor status and non-sentinel involvement.…”
Section: Discussioncontrasting
confidence: 60%
“…Öz et al (25) reported that Ki-67 and c-erb-B2 expression is connected with non-sentinel metastasis and also two other studies stated cerb-B2 as an independent factor (23,24). We found no direct relation between Ki-67, c-erb-B2, hormone receptor status and non-sentinel involvement.…”
Section: Discussioncontrasting
confidence: 60%
“…Hilusdaki yağlı değişiklikler tanımlanır. Hilusdan geçen ilk kesitlerde makroskopik görünür metastaz yok ise 3-4 mm'den kalın olan lenf düğümleri olabildiğince ince 2 mm'yi (2000 µm) geçmeyen aralar ile yine uzun eksene paralel dilimlenir, dikkatlice incelenir (3,4,11,28,29,30,31,32,33). Çoğunlukla hilusda yağlı değişiklikler geniş yer kaplar, frozen kesit için de sorun yaratacağından bu alan kortikal grimsi alandan kesilerek ayrılır (Resim 3).…”
Section: Sldb'sininoperasyonsırasındadeğerlendirilmesiunclassified
“…Kesit aralıkları merkezlere göre 10, 50, 100, 150, 200, 250, 500 μm arasında değişmektedir (3,5,11,28,33).…”
Section: Metastaz Saptanmayan Lenf Düğümlerinin İşlemealınmasıunclassified
See 2 more Smart Citations